Post Stroke Rehabilitation: - Roshanzamir, Sharareh (Galen Medical Journal, 2016)
The modern stroke rehabilitation programs focuses on specific bio-physiological targets. Modern rehabilitation programs mainly make use of its potential plasticity to compensate for injury. Constraint-induced movement therapy (CIMT), bilateral arm training, and task specific training of the paretic limb, are examples of rehabilitation techniques promoting brain neuro-plasticity. There are many tasks other than locomotor function to be addressed by rehabilitation team. Sensory deficits, speech deficits, dysphagia, memory loss, post stroke central pains and bowel and bladder derangements are among the most important of these challenges that makes a multidisciplinary approach to stroke patients necessary.Â 